Fast food as drivers for overweight and obesity among urban school children at Jakarta, Indonesia - Febriani, Dian; Sudarti, Trini (Jurnal Gizi dan Pangan, 2019)
The study aimed to analyse dominant factors associated with overweight and obesity among students in Perguruan Cikini Elementary School in Central Jakarta. A cross-sectional study was conducted between March-May 2017 with 145 participants from 3rd, 4th, and 5th grades. Data obtained were measurement of body weight and height, physical activity questionnaire for children, food frequency questionnaire and 24-hour food recall. Prevalence of overweight and obesity among students in Perguruan Cikini Elementary School in Central Jakarta was 41.4%. Based on logistic regression, fast food consumption was a dominant factor associated with overweight and obesity among students in Perguruan Cikini Elementary School in Central Jakarta. Students who consumed fast food >3 times/week were 2.42 times more likely to be overweight and obese compared to students who consumed fast food ≤3 times/week.